A cryptic mitochondrial DNA link between North European and West African dogs. (20th March 2017) - Adeola, Adeniyi C.; Ommeh, Sheila C.; Song, Jiao-Jiao; Olaogun, S. Charles; Sanke, Oscar J.; Yin, Ting-Ting; Wang, Guo-Dong; Wu, Shi-Fang; Zhou, Zhong-Yin; Lichoti, Jacqueline K.; Agwanda, Bernard R.; Dawuda, Philip M.; et al.
Abstract: Domestic dogs have an ancient origin and a long history in Africa. Nevertheless, the timing and sources of their introduction into Africa remain enigmatic. Herein, we analyse variation in mitochondrial DNA (mtDNA) D-loop sequences from 345 Nigerian and 37 Kenyan village dogs plus 1530 published sequences of dogs from other parts of Africa, Europe and West Asia. All Kenyan dogs can be assigned to one of three haplogroups (matrilines; clades): A, B, and C, while Nigerian dogs can be assigned to one of four haplogroups A, B, C, and D. None of the African dogs exhibits a matrilineal contribution from the African wolf ( Canis lupus lupaster ). The genetic signal of a recent demographic expansion is detected in Nigerian dogs from West Africa. The analyses of mitochondrial genomes reveal a maternal genetic link between modern West African and North European dogs indicated by sub-haplogroup D1 (but not the entire haplogroup D) coalescing around 12, 000 years ago. Incorporating molecular anthropological evidence, we propose that sub-haplogroup D1 in West African dogs could be traced back to the late-glacial dispersals, potentially associated with human hunter-gatherer migration from southwestern Europe.